Industrial training report: Majlis Perbandaran Port Dickson / Nurul Hazimah Rahmat - Rahmat, Nurul Hazimah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report of students’ industrial work experience for the Industrial Training course (IMD310) which has been carried out at Port Dickson Municipal Council from 22 July 2024 until 13 September 2024. This course must be taken by all students before completing our Diploma in Information Management in UiTM. This report also covers every activity that has been carried out in every unit, special projects, skills applied and all the tasks that students successfully perform during the two months of internship at Port Dickson Municipal Council. In addition, the report also has background information of the organization, departmental structure and function related the organization. The challenges faced by students, as well as the organizational issues and suggestions for improvement have all been clearly mentioned in this report. Besides, this paper also included appendices of the work that students learned.